The land crabs of the Discoplax longipes A. Milne-Edwards, 1867 species group, with description of a new species from Guam (Crustacea: Decapoda: Brachyura: Gecarcinidae) - Ng, Peter K. L.; Shih, Hsi-Te (Zootaxa, 2015)
Specimens of the gecarcinid land crab Discoplax longipes A. Milne-Edwards, 1867, from the western Pacific, can be separated into two distinct groups on the basis of DNA (mitochondrial 16S rDNA and cytochrome oxidase subunit I) and structure of the male first gonopod. On the basis of this data, the material that occurs from the Loyalty Islands to French Polynesia is shown to be D. longipes s. str., whereas specimens from Guam are here referred to a new pseudocryptic species, D. michalis n. sp. The two species are described and figured; and a revised key to the long-legged Discoplax species is provided.